Scrophularia striata Extract Supports Rumen Fermentation and Improves Microbial Diversity in vitro Compared to Monensin - Bagheri Varzaneh, Maryam; Klevenhusen, Fenja; Zebeli, Qendrim; Petri, Renee (Frontiers in Microbiology, 2018)
In the search for natural alternatives to antibiotic feed additives, we compared the efficacy of two doses of Scrophularia striata extract (S. striata-Low at 40 and S. striata-High at 80 mg g-1 dry matter) with monensin (monensin) and a negative control in the modulation of rumen fermentation, methane production and microbial abundance in vitro. Microbes were investigated using qPCR and 16S rRNA targeted sequencing. Data showed that the addition of S. striata increased production of total short chain fatty acids (SCFA) in comparison to both monensin and control (P = 0.04). The addition of S. striata increased acetate production, and increased propionate at the higher dosage (P < 0.001). Supplementation of S. striata lowered methane production (P < 0.001) compared to control but with no effect compared to monensin. Ammonia concentration decreased by 52% (P < 0.001) with S. striata-High supplementation (4.14 mmol L-1) compared to control, which was greater than that of monensin (36%). The diversity of rumen bacteria was reduced (P < 0.001) with monensin supplementation for both the number of observed OTUs and the Chao1 index. Quantitative analysis of Protozoa showed a decrease in the monensin treatment and an increase in the S. striata-High treatment (P = 0.05) compared to control. Archaea copy numbers decreased equally in both S. striata-High and monensin treatments compared to the control group. Supplementation with S. striata increased relative abundances of Fibrobacteres (P < 0.001) and Planctomycetes (P = 0.001) in comparison to both the control and monensin treatments. Significant negative correlations were observed between the abundances of Bacteroides, Fusobacterium and Succinivibrio genera and methane (r > -0.71; P ≤ 0.001). The abundance of Fibrobacter genera and total SCFA (r = 0.86), acetate (r = 0.75) and valerate (r = 0.76; P < 0.001) correlated positively. These results suggest that S. striata supplementation at 80 mg kg-1 DM inclusion, similar to monensin, supports rumen fermentation, lowers methane and ammonia production. However, unlike monensin, S. striata supported rumen fermentation toward higher total SCFA and propionate production, while still supporting a diverse rumen microbiome and an increase in cellulolytic bacteria such as Fibrobacter.